2017
DOI: 10.1007/s10803-017-3380-1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Social Tools And Rules for Teens (START) Program: An Immersive Socialization Intervention for Adolescents with Autism Spectrum Disorder

Abstract: Adolescents with ASD face numerous personal and contextual barriers that impede the development of social motivation and core competencies, warranting the need for targeted intervention. A randomized controlled trial was conducted with 40 adolescents to evaluate the merits of a multi-component socialization intervention that places emphasis on experiential learning. This investigation evaluated the impact of the 20-week START program on the social functioning of adolescents with ASD. Significant Group × Time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Improvement was determined by examining the recorded number of times the participant was using the skill in the past 5 weeks and also the facilitator's clinical judgment of whether it would be more beneficial to continue practicing the same skill or if another target skill was more pressing. Please see Vernon et al (2016) and Vernon et al (2018) for more details on target skills and self-management procedures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Improvement was determined by examining the recorded number of times the participant was using the skill in the past 5 weeks and also the facilitator's clinical judgment of whether it would be more beneficial to continue practicing the same skill or if another target skill was more pressing. Please see Vernon et al (2016) and Vernon et al (2018) for more details on target skills and self-management procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Future methods for unobtrusively gathering social performance data from participants in everyday social settings (perhaps in home, school, and community environments) would be essential to thoroughly evaluate generalized improvements. Fortunately, there is some existing evidence of convergent social competence improvements in parent and self-report data from the START program, which offers some support for the generalization of improvements to other settings (Vernon et al, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A search of the current literature evaluating SSGTs for adolescents via randomized controlled trials (RCTs), identified a number of design and intervention limitations. Consistent design limitations included small sample sizes (9,(27)(28)(29)(30)(31), failing to employ blinded or external observer-report measurement of dependent variables (17,20,27,29,30,(32)(33)(34)(35), failing to describe the randomization processes (27, 29-31, 33, 34) or employ allocation concealment (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), limited application of intent-to-treat data analysis (17,(27)(28)(29)(30)(32)(33)(34)(35), a lack of clarity in regard to compliance with the Consolidated Standards of Reporting Trials (CONSORT) statement (20,27,29,30,35,36), and limited examples of mixed methods studies integrating quantitative and qualitative data collection methods and analysis in understanding the outcomes of interventions…”
Section: Social Skills Group Trainingmentioning
confidence: 99%